Cardiac Resynchronization Therapy Device Implantation in a Patient with Congenitally Corrected Transposition of Great Vessels - Reza Mollazadeh (Journal of Tehran University Heart Center, 2017)
A 29-year-old woman was referred to our hospital due to exacerbation in dyspnea on exertion and easy fatigability. A known case of congenitally corrected transposition of the great vessels and congenital complete heart block, she had already received a permanent single-chamber pacemaker. Decision was made to implant a biventricular pacemaker for the treatment of the failing heart. Excellent coronary sinus lead implantation was done, conferring amelioration of symptoms, QRS narrowing in the electrocardiogram, and improvement of systemic ventricular systolic function in echocardiography. Over a 15-month follow-up period, she had no dyspnea on exertion. This case highlights the significance of upgrading pacemakers in patients with heart failure.